High frequency impedance measurements of sodium solid electrolytes. Issue 9 (August 2022) - Wagner, Dörte; Kusnezoff, Mihails; Schilm, Jochen; Heubner, Christian; Herrmann, Mathias; Weber, Andre; Braun, Philipp; Lee, Chang Woo; Shaji, Nitheesha
Abstract: Solid-state sodium batteries are currently gaining enormous interest as a lower-cost and more environmentally friendly alternative to lithium batteries. They contain significantly less critical rare elements in both the electrolyte and the active material. However, to date, there is no efficient material combination of metallic anode, cathode, and solid electrolyte for room temperature applications that does not require an additional liquid electrolyte while maintaining high energy density. NaPSiO-based glass-ceramics show high ionic conductivity at room temperature, good corrosion resistance against ambient humidity and CO2, and stability against metallic sodium. However, the conductivity mechanisms of this promising class of materials are currently poorly understood. Herein, high frequency impedance measurements up to 10 8 Hz shed light on the contributions of grains and grain boundaries to the total impedance, including the distribution of relaxation time constants of the fully crystallized material. In addition, analysis of the temperature dependence allows separation of electrode contributions and determination of activation energies for grain and grain boundary conductivities. Our study provides the basis for fine-tuning the stoichiometry of NaPSiO-based glass-ceramics in terms of maximizing the conductive phase fraction to optimize the performance of future solid-state sodium batteries.